Eddy variability and energetics from direct current measurements in the Antarctic Circumpolar Current south of Australia - Phillips, HE; Rintoul, SR (2000)
Two year time series measurements of current velocity and temperature in the Subantarctic Front (SAF) south of Australia from 1993 to 1995 provide estimates of eddy fluxes of heat and momentum across the Antarctic Circumpolar Current (ACC) and further insight into the variability of the ACC. The SAF was found to be an energetic, meandering jet with vertically coherent fluctuations varying on a timescale of 20 days with typical amplitude 30 cm/s at 1150 dbar. A daily-varying coordinate frame which follows the direction of ow allowed mesoscale variability of the SAF to be isolated from variability due to meandering of the front and proved very successful for examining eddy uxes. Vertically averaged cross-stream eddy heat flux was 11.3 kW/m^2 poleward and significantly different from zero at the 95% confidence interval for fluctuations in the 2-90 day band. Zonally integrated, this eddy heat flux (=0.9 PW) is more than large enough to balance heat lost south of the Polar Front and is as large as cross-SAF fluxes found in Drake Passage. Cross-stream eddy momentum fluxes were small, not significantly different from zero and of indeterminate sign, but tending to decelerate the mean flow. A relationship between vertical motion and meander phase identified in the Gulf Stream was found to hold for the SAF. Eddy kinetic energy levels were similar to those in Drake Passage and southeast of New Zealand. Eddy potential energy was up to an order of magnitude larger than other ACC sites, most likely because meandering of the front is more common here. Baroclinic conversion was found to be the dominant mechanism by which eddies grow south of Australia. Typical eddy growth rate is estimated to be 30 days, approximately twice as fast as in Drake Passage, consistent with eddy energy growing rapidly downstream.